Switzerland : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Switzerland's economy has performed relatively well in the aftermath of the global financial crisis, with growth reaching 2 percent in 2014. However, the economic environment became more complicated in late 2014, as increased capital inflows forced the Swiss National Bank (SNB) to start intervening heavily to defend its exchange rate floor of 1.20 francs per euro. Over the medium term, the economy is expected to recover gradually. As the economy adjusts to the exchange rate appreciation, growth is projected to rise gradually back to about 2 percent over the medium term while inflation increases to about 1 percent.